Story telling in bilingual Urdu−Cantonese ethnic minority children: Macrostructure and its relation to microstructural linguistic skills - Chan, Angel; Chen, Sarah; Hamdani, Saboor; Tse, Bernard; Cheng, Kelly (Frontiers in Psychology, 2023)
Introduction The ability to produce a well-structured, coherent and informative narrative requires the integration of lexical and grammatical skills at different levels of complexity. Investigating how narrative macrostructure competence is predicted by microstructural linguistic skills is conceptually enlightening; yet there have been very few, if any, studies documenting the associations between macrostructure and microstructure in both languages of the same bilinguals. In this paper we attempt to address this research gap and report on the first empirical study of Urdu-Cantonese bilingual children’s narrative abilities, bringing in data from a new language pair that is currently understudied. Methods Twenty-four bilinguals (mean age = 9.17 years) acquiring Urdu as first, family and heritage minority language, and Cantonese as second, school and majority language were assessed via Multilingual Assessment Instrument for Narratives (MAIN). We examined these children’s macrostructural competence and its relations to microstructural skills in both languages (Urdu and Cantonese). Three macrostructure components were scored as response variables: Story Structure (SS), Story Complexity (SC), Internal State Terms (IST). Four microstructural measures were scored as predictor variables: number of different words (NDW), mean length of Communication Units (MLCU), proportion of grammatical Communication Units (Gproportion), proportion of correct connectives linking the major episodic elements (Cproportion). Results In regression analyses, NDW emerged consistently as a positive predictor of SS, SC and IST in both languages. MLCU and NDW were positive predictors of SS in the stronger L1, but NDW was the only positive predictor of SS in L2. By contrast, NDW and an index of syntactic competence (MLCU in L1, but Cproportion in L2) were significant or close-to-significant positive predictors of SC in both languages. NDW was the only positive predictor of IST in both languages. These findings suggested that the relationships between narrative macrostructure and specific microstructural abilities could manifest both similarly and differently between L1 and L2. Discussion We discuss the findings by considering the unique nature of each macrostructure component and how each component might be related to specific microstructural linguistic skills. We suggest directions for further research and discuss how the current findings bring deeper implications for educators and clinicians in assessment, pedagogy, and intervention.